2023
DOI: 10.3390/jcm12031138
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Pregnancy: 2 Case Reports and a Systematic Review

Abstract: Ovarian pregnancy is a rare but well-known pathology. However, pathophysiology, diagnosis and treatment are not established. Therefore, all case reports on ovarian pregnancy published in PubMed from November 2011 till November 2022 were reviewed and two case reports were added. In these 84 case reports, 8% of ovarian pregnancies occurred in women without or with blocked oviducts and 23% were localised on the other side than the corpus luteum. Since symptoms are not specific, ovarian pregnancy has to be suspect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…de gestación, aunque se han descrito casos hasta pasadas las 44 semanas. En la actualidad, la precisión diagnóstica mediante estudios radiológicos no está lo suficientemente documentada (16).…”
Section: Gestación Ovárica Ectópica Y Subunidad β De Gonadotropina Co...unclassified
“…de gestación, aunque se han descrito casos hasta pasadas las 44 semanas. En la actualidad, la precisión diagnóstica mediante estudios radiológicos no está lo suficientemente documentada (16).…”
Section: Gestación Ovárica Ectópica Y Subunidad β De Gonadotropina Co...unclassified
“…An ovarian ectopic pregnancy (OEP) is a rare form of ectopic pregnancy that is implanted completely or partially within the ovarian parenchyma 1 . A recent systematic review 2 identified only 82 case reports of OEP in the international literature between 2011 and 2022. Although non‐invasive diagnosis of ectopic pregnancy at other sites, such as tubal ectopic pregnancy (TEP) or Cesarean scar pregnancy, has improved in recent years, OEP is still detected mostly at emergency surgery.…”
Section: Introductionmentioning
confidence: 99%